Ethics And Professionalism Of Judges In Dealing With Non-Procedural Lawyers: A Case Study In Religious Courts Purbalingga - Muhammad, Syafik; Vauzi, Nur Kholis; Muzaki, Muhammad Zain; Malihatunnisa, Ade; Fatkhanah, Fatkhanah; Saputri, Apik Anitasari Intan; Ali, Nur (DAS Institute, 2025)
This study aims to analyze the dynamics of disorderly conduct by legal counsel during court proceedings and examine the ethical and professional responses of judges to such non-procedural behavior. Disruptions caused by legal counsel in the courtroom not only hinder the judicial process but also pose significant challenges for judges in maintaining the dignity and order of the proceedings. Using a qualitative approach through case studies within the religious court system, this research explores various forms of misconduct, judicial responses, and the extent to which the principles outlined in the Code of Ethics and Judicial Conduct (KEPPH) are practically implemented. Furthermore, a theoretical analysis of judicial professionalism and ethics is conducted to assess the alignment between normative ideals and actual courtroom practices. The findings indicate that misconduct by legal counsel manifests in various forms, ranging from breaches of decorum to non-procedural interruptions. Judicial responses vary depending on the severity of the misconduct and the individual character of each judge. This study concludes that the synergy between professionalism and judicial ethics is fundamental to maintaining the credibility of the judicial system. Therefore, the development of guidelines for handling non-procedural behavior, along with the enhancement of ethical and character-based training for legal practitioners, is strongly recommended.